2009
DOI: 10.1080/03602550903147247
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Polypropylene for Production of Eco-Composites

Abstract: Renewable raw materials and recyclable thermoplastic polymers provide attractive eco-friendly quality as well as environmental sustainability to the resulting natural fiber reinforced composites. We studied the possibility of using the recycled polypropylene (PP) for production of composites based on kenaf fibers (KF) and rice hulls (RH) as reinforcements. Polypropylene/rice-hulls (PP/ RH/CA) and polypropylene/kenaf (PP/K/CA) composites with 30% fiber (filler) content and appropriate compatibilizing agent (CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Now, natural fibers have been widely used in WPCs [6][7][8][9] . In the previous literatures, some non-wood fibers, such as bast (kenaf, hemp, flax fibers [10] , jute fiber [11,12] , henequen fiber [13] , banana fiber [14] ), leaf (sisal [13] ), seed or fruit fibers (castor presscake [15] , olive pomace [16] , rice hulls [17] , silk and cotton waste [18] ), and bamboo powder=flour [19][20][21] have been widely used to prepare WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Now, natural fibers have been widely used in WPCs [6][7][8][9] . In the previous literatures, some non-wood fibers, such as bast (kenaf, hemp, flax fibers [10] , jute fiber [11,12] , henequen fiber [13] , banana fiber [14] ), leaf (sisal [13] ), seed or fruit fibers (castor presscake [15] , olive pomace [16] , rice hulls [17] , silk and cotton waste [18] ), and bamboo powder=flour [19][20][21] have been widely used to prepare WPCs.…”
Section: Introductionmentioning
confidence: 99%
“…The production procedures for natural fiber composites are quite similar to those for the production of conventional glass fiber composites, and they include injection and compression molding, vacuum injection molding, structural reacting injection molding and resin transfer molding [94,[106][107][108]. In PP-based composites, natural fibers are used in the form of nonwoven textiles, fabrics, mat, SMC (sheet molding compounds) and BMC (bulk molding compounds) for compression molding, and hybrid mats (both the reinforcement and the matrix polymer are in fibrous form), but also as UDreinforcing fibers [109].…”
Section: Pp Nanofibers -A New Important Class Of Materialsmentioning
confidence: 99%
“…Bagasse/polypropylene and china reed/PP composites contribute to further weight reduction and energy saving compared to glass fiber reinforced plastics [92]. Currently, the widely favored PP is used for great number of recyclable eco-composites [95,[106][107]. Although PP could not be classified as a biodegradable polymer, by introducing thermo-sensitive catalysts to increase its degradability (as reported earlier in this paper), PP continues to take an important place in ecocomposite materials.…”
Section: Pp Nanofibers -A New Important Class Of Materialsmentioning
confidence: 99%
“…Considerable research has focused on composites made from recyclable polymers combined with kenaf fibers (Srebrenkoska et al 2009). It was reported that thermal stability and flexural modulus of the composite improved when 5% esterified lignin was added to the recycled polystyrene (Pérez-Guerrero et al 2014); similar results have been reported with the addition of unmodified kraft lignin (Schorr et al 2015).…”
Section: Introductionmentioning
confidence: 99%